Practice Communication Governance Studies: A Systematic Literature Review - Safitri; Salahudin (Journal of Governance and Administrative Reform, 2024)
Abstract The objective of this study is to examine communication practices using the Systematic Literature Review (SLR) method. This study utilizes SLR, drawing on 70 scientific articles from the Scopus database. The Vosviewer application is employed to analyze and visualize the data. The research results indicate that the adoption rate of digital technology and the success of implementing sustainable practices vary across different villages. This includes adopting renewable energy, using smart sensors for environmental monitoring, and developing digital infrastructure to enhance public services. These findings deepen our understanding of the dynamics and challenges in government communication practices. This research contributes to the development of a comprehensive research agenda on communication management issues. It provides a solid foundation for advancing government communication theory and practice by offering an extensive overview of the practices discussed in the literature. However, this study has limitations, primarily that the articles are sourced exclusively from the Scopus database. Therefore, the research results may not comprehensively cover government communication issues. Integrating articles from leading international databases such as Web of Science and Dimensions Scholars could provide a broader and more in-depth view of government communication issues. Web of Science is a leading dataset in the field with thousands of globally indexed articles and journals, while Dimensions Scholars offers information from a wide range of disciplines. Including these sources would enhance the validity and generalizability of the findings, making a greater contribution to developing effective government communication practices and policies aligned with societal needs.  Keywords: practice, communication, governance   Abstrak Tujuan dari penelitian ini adalah untuk mempelajari praktik komunikasi pemerinrahan yang berfokus pada penggunaan metode Sistematic Literature Review (SLR). Penelitian ini menggunakan SLR, yang menggunakan 70 artikel ilmiah dari databse scopus. Aplikasi Vosviewer digunakan untuk menganalisis dan menampilkan data selama review artikel. Hasil penelitian menunjukkan bahwa tingkat adopsi teknologi digital dan keberhasilan penerapan praktik berkelanjutan berbeda-beda di berbagai desa; adopsi energi terbarukan, penggunaan sensor pintar untuk pemantauan lingkungan; dan pengembangan infrastruktur digital untuk meningkatkan layanan publik. Hasil-hasil ini meningkatkan pemahaman kita tentang dinamika dan masalah dalam praktik komunikasi pemerintahan. Penelitian ini membantu mengembangkan garis besar penelitian tentang masalah manajemen komunikasi. Penelitian ini memberikan landasan yang kuat untuk kemajuan teori dan praktik komunikasi pemerintahan dengan memberikan gambaran menyeluruh tentang praktik yang telah dibahas dalam literatur terkait. Tetapi studi ini memiliki keterbatasan. Salah satunya adalah artikel yang digunakan hanya bersumber dari database Scopus, sehingga hasil penelitian tidak dapat mencakup masalah komunikasi pemerintahan secara menyeluruh. Menggabungkan artikel ilmiah dari database internasional terkemuka seperti Web of Science dan Dimensions Scholars akan memberikan pandangan yang lebih luas dan mendalam tentang masalah komunikasi pemerintahan. Web of Science adalah salah satu database terkemuka dalam bidang dengan ribuan artikel dan jurnal yang terindeks secara global, sementara Dimensions Scholars menyediakan informasi dari berbagai disiplin ilmu, memungkinkan untu Penelitian lanjutan dapat meningkatkan validitas dan generalisasi temuan dengan melibatkan sumber-sumber ini. Hal ini akan memberikan kontribusi yang lebih besar untuk membangun praktik komunikasi pemerintahan dan kebijakan yang efisien dan sesuai dengan kebutuhan masyarakat. Kata kunci: praktik, komunikasi, pemerintahan.